The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1038/s41598-019-38477-y
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Aerosol Deposition Process for flexible electronic device and determining the Film Formation Mechanism with Cushioning Effects

Abstract: In this paper, we demonstrated the feasibility of the Aerosol Deposition (AD) method which can be adapted as a future fabrication process for flexible electronic devices. On the basis of this method’s noticeable advantages such as room-temperature processing, suitability for mass production, wide material selectivity, and direct fabrication on a flexible substrate, we fabricated and evaluated a flexible conductive bridge random access memory (CBRAM) to confirm the feasibility of this method. The CBRAM was fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Due to the thickness limitation, conventional mechanical testing methods on a macroscopic scale, for example, flexural bending tests, are not applicable to AD films. In this regard, indentation tests, including nanoindentation and Vickers indentation, are more favorable for the investigation of mechanical properties of AD films 29,30 . In the specific case of AD‐BT films, nanoindentation has been performed by Kim et al 29 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the thickness limitation, conventional mechanical testing methods on a macroscopic scale, for example, flexural bending tests, are not applicable to AD films. In this regard, indentation tests, including nanoindentation and Vickers indentation, are more favorable for the investigation of mechanical properties of AD films 29,30 . In the specific case of AD‐BT films, nanoindentation has been performed by Kim et al 29 .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, indentation tests, including nanoindentation and Vickers indentation, are more favorable for the investigation of mechanical properties of AD films. 29,30 In the specific case of AD-BT films, nanoindentation has been performed by Kim et al 29 to correlate surface morphologies and dielectric properties to film hardness as well as finding the boundary of minimum film thickness with AD-BT films in terms of acceptable leakage current. However, only the as-processed state has been covered in the previous study, leaving open questions regarding the mechanical properties of the film following thermal treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that that the SAY particle broke with the partially damaged substrate immediately after impact. Subsequently, broken SAY particles were anchored in the glass substrate due to the generated thermal energy [13]. The interface of STS304 was observed as a film surrounding the substrate surface (Figure 4(c)), unlike the case of the Al 2 O 3 and glass substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that when particles accelerated by a carrier gas collide with the substrate, the kinetic energy is converted to impact energy [8,11,12]. At this time, the particles are crushed by the impact energy, which instantaneously generates thermal energy at the contact point of the crushed particles, anchoring them to the substrate [13,14]. Therefore, the initial coating layer state is affected by the hardness of the substrate.…”
Section: Introductionmentioning
confidence: 99%
“…The sensor is fabricated by a one-step aerosol deposition (AD) process, which has numerous advantages, such as fast coating speed, film deposition at low vacuum, full-room-temperature process without any heat treatment, and rigid film-to-substrate adhesion [37][38][39]. The AD process has considerable advantages over conventional technologies because a composite film can be easily prepared by simply mixing and loading more than two materials [40][41][42]. The AD principle is defined by the hammering effect, wherein high-speed particles continuously collide with pre-deposited layers; consequently, the internal density is dominated by the layer thickness and mechanical properties of each material [43,44].…”
Section: Introductionmentioning
confidence: 99%